"From Our Little School, Making That Revolution Happen." Evaluation of Basic Education Teachers in a Continuing Education Diploma Program with a Gender Perspective (Praxis Educativa, 2025)
This paper examines the assessments of teachers who participated in a continuing education diploma program with a gender perspective. The program aimed to raise awareness among elementary school educators about gender issues and promoted critical reflection to reframe and integrate this perspective into their teaching practices. This study followed a descriptive qualitative research design. Semi-structured interviews were conducted with 12 teachers from preschool, primary, and secondary education levels who completed the program. The analysis explores positive aspects, challenges, areas for improvement, and the overall relevance of the program. Findings highlight the key role of facilitators, the need to create spaces that encourage peer knowledge exchange, self-directed learning, and sustained reflection on teaching practices. Additionally, the study identifies gender-based barriers that hinder teachers’ participation in continuing education.
Keywords: qualitative analysis; education; permanent education; teacher training; pedagogical practice